Local Wisdom-based Approaches for Disaster Risk Reduction in Urban Communities: Insights from Kampung Kuta - Anita Eka Putri; Dwiyono Hari Utomo; Budi Handoyo; Syamsul Bachri; Rajendra Prasad Shrestha; Ravinesh Rohit Prasad; Ruli As'ari; Zumrotin Nisa (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2026)
Aims: This study aimed to develop an approach for disaster risk reduction in urban communities of the indigenous community in Kampung Kuta, West Java, to enhance disaster literacy. The primary issue addressed was the insufficient integration of traditional knowledge into formal disaster education, limiting the effectiveness of disaster preparedness in local communities. Methodology and Results: The study highlighted the inadequate integration of traditional knowledge into formal disaster mitigation, hampering the effectiveness of disaster preparedness in indigenous communities. A qualitative approach was employed, involving interviews, observations, and focus group discussions (FGDs) with local indigenous leaders and community members. The results reveal that Kampung Kuta's indigenous knowledge offers valuable practices for disaster mitigation, such as environmental management and communal responsibility, which could be integrated into formal mitigation frameworks. Transforming these traditions into resilience learning strategies could significantly enhance disaster literacy, fostering greater awareness and resilience within the community. The novelty of this research lies in the fusion of traditional and modern educational strategies, creating culturally relevant disaster education approaches that preserve indigenous knowledge and enhance its application in contemporary disaster management. Conclusion, Significance, and Impact: This strategy provides a viable model for other regions with strong traditions of local wisdom, contributing to the global discourse on integrating indigenous practices into disaster risk reduction (DRR) frameworks, especially in areas prone to natural disasters.